2014
DOI: 10.1371/journal.pone.0102950
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vitreous Imaging in Healthy Eyes Using Swept Source Optical Coherence Tomography

Abstract: PurposeTo describe enhanced vitreous imaging for visualization of anatomic features and microstructures within the posterior vitreous and vitreoretinal interface in healthy eyes using swept-source optical coherence tomography (SS-OCT). The study hypothesis was that long-wavelength, high-speed, volumetric SS-OCT with software registration motion correction and vitreous window display or high-dynamic-range (HDR) display improves detection sensitivity of posterior vitreous and vitreoretinal features compared to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 22 publications
1
52
0
1
Order By: Relevance
“…Since then, several publications have used SS-OCT to examine the vitreous in health and disease. [9][10][11][12][13][14] However, although the premacular bursa and its relationship to Cloquet's canal have been the subject of relatively intense study, 2,9,10 PVF and vitreous cisterns have not been described using this noninvasive imaging method. The aim of this study was to characterize PVF and vitreous cisternal spaces in vivo with SS-OCT imaging, which may be relevant to vitreoretinal interface diseases and vitreous pharmacodynamics.…”
mentioning
confidence: 99%
“…Since then, several publications have used SS-OCT to examine the vitreous in health and disease. [9][10][11][12][13][14] However, although the premacular bursa and its relationship to Cloquet's canal have been the subject of relatively intense study, 2,9,10 PVF and vitreous cisterns have not been described using this noninvasive imaging method. The aim of this study was to characterize PVF and vitreous cisternal spaces in vivo with SS-OCT imaging, which may be relevant to vitreoretinal interface diseases and vitreous pharmacodynamics.…”
mentioning
confidence: 99%
“…The recent use of wide fi eld three-dimensional swept source OCT (SS-OCT), which utilizes better sensitivity with imaging depth and longer imaging range, has enabled enhanced imaging of vitreous and vitreo-retinal interface. SS-OCT can offer superior resolution of vitreo-retinal entities, such as Bergmeister's papillae that may simulate papilledema [ 67 ].…”
Section: Pseudopapilledema: Bergmeister's Papilla and Myelinated Nervmentioning
confidence: 99%
“…22 Using SS-OCT, recent studies demonstrated an ability to better visualize the posterior vitreous and vitreoretinal interface in healthy eyes and determined the prevalence and described the dimensions and shapes of the bursa premacularis and area of Martegiani. 2325 A more detailed three-dimensional analysis of the posterior vitreous and vitreoretinal interface using volumetric SS-OCT with a high A-scan density acquired over a wide field of the retina covering the fovea and the optic nerve head regions was recently demonstrated by Liu JJ et al 26 In this study, 26 a vitreous windowing method was employed to enhance the details of the vitreous, and various features of the posterior vitreous and vitreoretinal interface in young healthy eyes were described. Another recent SS-OCT study examined the vitreoretinal interface in 4 patients with PDR and described features such as neovascularization and vitreoschisis.…”
Section: Introductionmentioning
confidence: 98%